Manufacturer adoption of a unilateral pricing policy in a multi-channel setting to combat customer showrooming - Raj, S. P.; Rhee, Byong Duk; Sivakumar, K. (Journal of Business Research, 2020)
Unilateral pricing policy (UPP), in which the manufacturer mandates a minimum retail price for all retailers, has become increasingly popular. Manufacturers employ this pricing policy to encourage brick-and-mortar retailers to offer a high level of service in their stores and to support brick-and-mortar retailers that provide presales services for customers in the presence of showrooming—a phenomenon in which a customer visits an offline retailer to learn about the product but purchases from an online retailer for a lower price. Our proposed analytical model identifies the motivations of a UPP and helps determine the approach to setting a UPP-based price under various conditions. The UPP price depends on key factors such as the extent of showrooming in the market, customer price sensitivity, and the salience of presales service in their valuation. We compare the outcomes of a UPP with those under the conventional policy, in which the retailers determine prices independently.
Keywords: Channel competition; Offline presales service; Pricing; Showrooming; Unilateral pricing policy